EFEKTIFITAS HYPNOBIRTHING PADA IBU BERSALIN TERHADAP NILAI APGAR SATU MENIT PERTAMA BAYI BARU LAHIR DI KABUPATEN CIREBON - Yeni Fitrianingsih (Universitas Tribhuwana Tunggadewi, 2014)
Hypnobirthing can be used to deal with and go through pregnancy and childbirth preparation in a natural, relaxing, and comfortable way and to be useful in helping to supply oxygen to the baby during childbirth so that the babies born have better Apgar score. This study aimed to determine the effect of hypnobirthing on the Apgar score on normal primiparous parturient in Cirebon. This was a quasi experimental study using a post -test only with control group design. Samples were taken with consecutive sampling technique which amounted to 60 people consisting of 30 people in the intervention group and 30 people in the control group. The effect of hypnobirthing on the Apgar score was analyzed using unpaired Mann-withney. The results showed that there were significant differences in the first Apgar mean score (the first minute) among respondents who were given hypnobirthing with those not given hypnobirthing (p = 0.000) and there were no significant differences in the second Apgar mean score (5 minutes later) among respondents who were given hypnobirthing with those not given hypnobirthing (p = 0.792). The author suggests that midwives be able to apply hypnobirthing to pregnant women in their third trimester of pregnancy in order to reduce the occurrence of asphyxia in newborns